Livestock breeding: the past, the present and the future - Haron, Abd Wahid (Universiti Putra Malaysia Press, 2013)
Successful livestock breeding until production of a healthy offspring is one of the key factors in ensuring sustainable animal production. The use of assisted reproductive biotechnology such as artificial insemination has always been practiced in ruminant sectors worldwide but its application in Malaysia is limited among farmers who are able to envisage the benefit of the technology in upgrading the genetic quality of their animals. The success of artificial insemination involves many factors such as semen collection, semen cryopreservation, handling of cryopreserved semen, insemination time and establishment of pregnancy. Therefore, this lecture dwells around research findings in the many processes in semen collection and cryopreservation which eventually improving the quality of semen prior to artificial insemination. It also discusses other aspects of livestock breeding such as oestrus synchronization and pregnancy diagnosis as well as in vitro embryo production.